PENINGKATAN EFISIENSI PUPUK FOSFAT MELALUI APLIKASI MIKORIZA PADA KEDELAI - INDAH PERMANASARI; KARTIKA DEWI; MOKHAMAD IRFAN; AHMAD TAUFIQ ARMINUDIN (Jurnal Agroteknologi, 2016)
The research purpose to investigate effect of mychorriza and phosphor dosage on growth and yield of soybean. The research was conducted in field experimental of Agriculture and Animal Science Faculty of State Islamic Univesity of Sultan Syarif Kasim Riau started from April to July, 2015. The planting media was peat soil with a pH of 4,79 and seeds used black soybean Mallika Varieties .The research was used Randomized Block Design with two factorials and four replications, the first factor was the dosage phosphor e.g. 0, 75, 150 kg/ha whereas the second factor was mychorriza consisted of 0, 20, 40, 60 g/polybag. The following parameter were observed e.g plant heigh, persentase mycorrhiza infection, number and weight of root nodules, number of pods/plant, number of seed/plant, weight dry seed/plant, weight dry plant, weight dry root, time of flowering and age of harvest time. The result showed that mychorriza application did not increased phsophor efficiency on soybean yield. Without mychorriza and phosphor 150 kg/ha increased shott-root ration at 80 days after planting.